Cytogenetic of skink (Reptilia, Scincidae) from Thailand: II: Chromosome analyses of stripe tree skink (Lipinia vittigera) - Patawang I. (2017)
© 2017 The Japan Mendel Society. Chromosomal analyses of the stripe tree skink (Lipinia vittigera Boulenger, 1894) from mitotic and meiotic cell divisions were studied. Bone marrow and testis samples were taken from five male and five female skinks. Skink chromosome preparations were conducted by squash technique from bone marrow and testis. The chromosomes were stained by conventional staining and Ag-NOR banding techniques. The results showed that the diploid chromosome number of L. vittigera was 2n=28, and the fundamental number (NF) was 44 in both males and females. The types of chromosomes were present as 8 large metacentric, 2 medium metacentric, 6 small metacentric macrochromosomes, and 12 microchromosomes. There was no observation of strange size chromosomes related to sex. Nucleolar organizer regions (NORs) appear to the telomere on the long arm of the largest metacentric chromosome pair 1 and medium metacentric chromosome pair 5. We found that during metaphase I on meiosis, the homologous chromosomes showed synapsis, which can be defined as the 14 bivalents and 14 haploid chromosomes at metaphase II as diploid species. The karyotype formula of L. vittigera is as follows: {equation presented}